LITERATURE REVIEW : EFISIENSI PERANGKAT TUNED MASS DAMPER (TMD) UNTUK MEREDUKSI RESPON DINAMIS JEMBATAN GANTUNG - Bayuyudo, Zafira Jovita; Pratiwi, Hilda Febriyani; Istiqomah, Istiqomah (Universitas Pendidikan Indonesia (UPI), 2025)
Suspension bridges, as one type of vital infrastructure with long spans, often withstand challenges in the form of dynamic vibrations caused by pedestrian loads, vehicles, wind, or earthquakes. These vibrations can cause problems ranging from discomfort to structural damage. One effective solution to reduce these vibrations is to use a Tuned Mass Damper (TMD). TMD is a passive device designed to reduce dynamic response by adjusting the mass, springs, and dampers, thereby increasing the stability and performance of the bridge. This paper uses a literature study method with the aim of analyzing the TMD reduction system on the dynamic response of suspension bridge structures and to determine the efficient device parameters for reducing the dynamic response of the structure. Through theoretical understanding and literature studies, it is obtained that TMD can significantly increase the damping ratio of the structure, although its performance is highly dependent on design parameters such as mass ratio, tuning frequency, and damping ratio. Parameter analysis shows that increasing the distance factor significantly improves the local performance of TMD, TMD tuning errors can significantly reduce its effectiveness so that there is an analysis of the effectiveness of each parameter. Keywords: Damping Efficiency, Design Parameters, Dynamic Vibration, Suspension Bridge, Tuned Mass Damper